Diagnoza i terapia głosu – ujęcie holistyczne. Wskazówki metodyczne oraz studium przypadku - Walencik-Topiłko, Anna (Logopaedica Lodziensia, 2023)
Voice is the subject of interest of several scientific and practical disciplines, including speech therapy, phoniatrics, vocal studies, choral conducting, acoustics. This study presents a speech therapy approach of the voice, emphasising the importance of the holistic approach. The author will introduce it as a methodologist and voice therapist – practitioner, conducting various types of classes in the field of voice: prevention, diagnosis and therapy. Methodological considerations were supported by a thematic case study.